2020
DOI: 10.7759/cureus.7183
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Perception, and Prevention Practices Related to Human Papillomavirus-based Cervical Cancer and Its Socioeconomic Correlates Among Women in Karachi, Pakistan

Abstract: Background Cervical carcinoma is a widespread disease of the female genital tract, for which human papillomavirus (HPV) is an utmost risk factor. Of the total global burden, the majority is endured by the developing nations of the world, mainly due to inadequate knowledge regarding the disease and ineffective measures taken for its prevention, early detection, and screening. Hence, our study aimed to determine the level of knowledge, general attitudes and perception, and prevention practices related to HPV-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
19
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 23 publications
11
19
2
1
Order By: Relevance
“…The results regarding the awareness of the relation between the HPV infection and CC showed inadequate knowledge about CC epidemiology compared to other studies conducted on Arab and non-Arab communities 17 , 21 , 22 .…”
Section: Discussioncontrasting
confidence: 71%
“…The results regarding the awareness of the relation between the HPV infection and CC showed inadequate knowledge about CC epidemiology compared to other studies conducted on Arab and non-Arab communities 17 , 21 , 22 .…”
Section: Discussioncontrasting
confidence: 71%
“…Our study findings showed that majority (90.1%) of the participants were knowledgeable of the term cervical cancer which is higher when compared with other similar studies in developing countries such as Pakistan, Ethiopia, and Zambia and where the percentage of participants knowledgeable of the term cervical cancer were 51.3, 76.8, and 36.8%, respectively (29,37,38). The variation may be attributable to the dissemination of information through various mass media and the availability of screening programs in Ghana.…”
Section: Discussioncontrasting
confidence: 48%
“…These three cities were chosen due to their population density and the availability of cervical cancer screening programs. The questionnaires were designed after a comprehensive review of literature from past studies and then approved by experts ( 27 29 ). The soundness and legitimacy of the questionnaire were further verified by a review panel of two experts each in oncology, gynecology and obstetrics, and research methodology prior to the pilot survey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is higher than in the study in neighboring Romania among women in the general population, that showed that just under 65% of women know that HPV can be transmitted through sexual contact, with both studies having a similar mean age of the participants [6]. Besides, our participants knew that the HPV transmission can be prevented by a condom, that risk of infection increase with several sexual partners and that, besides cervical cancer, HPV can cause genital warts, which is comparable with results of other studies [20]. However, in our study, only one-quarter of the sample knew that HPV cannot be transmitted through towels, toilets, or swimming pools and almost only one in eight participants knew that HPV infections can be cured spontaneously.…”
Section: Discussionsupporting
confidence: 87%